FOLIAGE OF Erythrina americana (Miller) AND Gliricidia sepium (Jacq.) Walp., SOURCE OF TANNINS: IMPLICATIONS OF ITS CONSUMPTION BY OVINE - Oliva Hernández, Jorge; Castillo Linares, Erika Belem; López Herrera, María Aurelia; Vélez Izquierdo, Alejandra (Kuxulkab', 2022)
'E. americana' and 'G. sepium' are tree legumes with multiple uses in agricultural and livestock farms in the humid tropical region of Mexico; however, its use as a feed for sheep is still scarce. The foliage of these legumes, in addition to a high nutritional value, also contains metabolites, important for the vital functions of plant cells, for the defense mechanisms of the plant, and for its adaptation to adverse weather conditions. Tannins are a type of secondary metabolite associated with both benefits and harm to the health and production efficiency of the animals that consume them. The objective of this work is to describe the interactions of tannins with microorganisms and parasites that inhabit on the rumen; highlighting its possible effects on health, productive efficiency and environmental impact, derived from its consumption through the diet and plant extracts.
Keywords: Secondary metabolites; Microorganisms; Diet; Ovine